ANALISIS NERACA AIR LAHAN UNTUK PENGEMBANGAN KEDELE DI KECAMATAN RANOMEETO BARAT KABUPATEN KONAWE SELATAN - ERAWAN, DEDI (Jurnal Agroteknos, 2023)
In order to develop soybean plants, the availability of water in the form of soil moisture is one of the factors that give a very important message. Water supply is usually obtained from rainwater, so the arrangement of cropping pattern often follows the pattern of rainfall distribution that occurs. Preparation of water balance is intended to increase the productivity of dry land through the determination of pattern and planting schedule in accordance with groundwater availability. The water balance analysis using climate data series includes monthly rainfall and air temperature. Climate data obtained from Climatology Station Wolter Monginsidi Kendari Southeast Sulawesi. The opportunity for rainfall is exceeded and the water balance is analyzed using statistical methods. The results show that the soil moisture conditions are available for the crops for 8 months, ie from December 10 daily 2 to July 10 daily 2. while the water deficit in August to November (during dry season). Thus the cultivation can be done for 8 months ie when a surplus of water.